Collaboration: Developing integration in multipurpose services in rural New South Wales, Australia - J K Anderson; A Bonner; J Grootjans (Rural and remote health, 2011)
The Multi-purpose Service (MPS) Program was introduced to rural Australia in 1991 as a solution to poor health outcomes in rural compared with metropolitan populations, difficulty in attracting healthcare staff and a lack of viability and range of health services in rural areas. The aim of this study was to describe the main concerns of participants involved in the development of multi-purpose services in rural New South Wales (NSW). This article is abstracted from a larger study and discusses the extent to which collaboration occurred within the new multi-purpose service.